Reshaping the Contours of State Responsibility for Employing Private Military Companies: a Case Study Analysis of Russia’s Role in Wagner’s Activities in Ukraine - Iurie Patricheev (Groningen Journal of International Law)
This study investigates legal accountability of the Russian Federation for private military company (PMC) Wagner’s actions in Ukraine, highlighting the applicability and limitations of customary international rules on state responsibility. Using a case study methodology, it examines Wagner's operational role in Ukraine and its complex relationship with the Russian state, applying Articles on Responsibility of States for Internationally Wrongful Acts (ARSIWA) as a theoretical framework. The findings reveal that current international law, codified in ARSIWA's rules on attribution, does not provide a framework for attributing Wagner's actions to the Russian Federation. Wagner does not function as an organ of the State (ARSIWA’s Article 4), nor does it meet the criteria for ‘effective control’ (ARSIWA’s Article 8), as required by customary rules on attribution in international jurisprudence. This legal framework's inability to address the nuanced and evolving nature of PMCs' involvement in State military activities points to a significant gap in international law. In response, the author proposes a four-step test under ARSIWA’s Article 8 for determining State control over PMCs. This test includes assessing the PMC's material dependency on the State, the degree of communication between the PMC and the state, the state's involvement in the PMC's strategic decision-making, and the PMC’s integration in the state's military manoeuvres. This approach seeks to reconcile the criteria of the ‘effective control’ and ‘overall control’ tests, aiming to more accurately reflect the realities of modern warfare and State-PMC relationships. Wagner members do not join for ideological reasons. They join for money.